MATHEMATICAL MODEL OF RICE COMMODITY SUPPLY CHAIN IN INDONESIA - Usdianto, Dwitama Alphin; Setiyowati, Ririn (PATTIMURA UNIVERSITY, 2023)
Food is the main need for every individual that must always be fulfilled. For Indonesia, food is identified with rice because this type of food is a commodity consumed by the Indonesian population. Therefore, the rice crisis can be interrupt economic resilience and national stability. National rice consumption from year to year will continue to increase in line with the increase in Indonesia's population. Although, Indonesia is the third-largest country in the world in producing the most, Indonesia still depends on rice imports. This was done by the government to maintain the national rice supply.The rice supply chain in Indonesia has not been optimum, as indicated by the relatively small profits of producer. In this research, we construct the maximum profit model of direct and indirect media sales of rice for producer, distributor, and retailer. And then, we determine the optimum solution of the model and analysis of the factors in the rice supply chain that affect it. The results showed that changes in the proportion of demand greatly affects the resulting optimal profit.